Sellar Metastasis of Cervical Adenocarcinoma. (10th January 2019) - Ravindran, Krishnan; Zsigray, Brandon M.; Wemhoff, Michael P.; Spencer, John D.; Borys, Ewa; Patel, Chirag R.; Germanwala, Anand V.
Abstract : Background . Pituitary metastasis of cervical adenocarcinoma is an exceedingly rare phenomenon. Case Description . The authors present a case of a 66-year-old female with cervical adenocarcinoma who was discovered to have a rapidly growing intrasellar mass in the work-up of adrenal insufficiency and hypothyroidism. The patient underwent subsequent endoscopic endonasal subtotal resection of the mass. Histopathological analysis of the resected lesion demonstrated features consistent with metastatic mucinous adenocarcinoma of the cervix. While initially neurologically asymptomatic following surgery, the patient developed an oculomotor nerve palsy several weeks following surgical debulking, at which time neuroimaging revealed marked regrowth and suprasellar extension of the metastatic lesion. Conclusions . While metastatic cervical adenocarcinoma to the sella is rare, it should be considered in the differential based on the history of the patient.